Restructuring of the Code of Ethics for the Protection of Human Rights in the Investigation of Suspects by the Indonesian National Police - Dwi Listyandarti; Wieke Dewi Suryandari; Irfan Rizky Hutomo (Journal Customary Law, 2026)
The protection of human rights (HAM) in the criminal justice system is a fundamental aspect that must be guaranteed by all law enforcement officers, including the Indonesian National Police (Polri). In suspect examinations, human rights principles often face challenges in their implementation, both due to regulatory weaknesses and field practices. One important instrument that plays a role in ensuring human rights protection during suspect examinations is the police code of ethics. This code of ethics regulates the standards of behavior and moral obligations that every member of the Polri must adhere to in conducting their duties. However, there are still gaps in the Polri code of ethics that have the potential to lead to human rights violations, such as the use of violence, intimidation, or misuse of power when questioning suspects. In order to guarantee that every police activity during suspect exams complies with applicable legislation and human rights principles, it is imperative that the code of ethics be reorganized. The study adopts a normative juridical approach, which is legal research that focuses on the assessment of legal doctrines and norms pertaining to the protection of human rights during police questioning of suspects. The National Police Chief's Regulation on the professional code of ethics and Law Number 2 of 2002 concerning the Indonesian National Police are two examples of primary legal materials that were used as data sources. Secondary legal materials included literature, scientific journals, and other legal documents. This approach is used to examine the extent to which the current National Police code of ethics protects the human rights of suspects and how an ideal restructuring concept can be implemented to strengthen this protection. The results are expected to provide concrete recommendations for updating the National Police code of ethics to be more oriented towards human rights protection and in line with the principle of due process of law in the criminal justice system.